Computer-Assisted Cognitive Training for ADHD: A Case Study - Kotwal, Dilnavaz B (Behavior modification, 1996)
Describes a computer-assisted cognitive training program used to treat a 13-year-old Caucasian male with attention deficit hyperactivity disorder. Pre-/posttest differences on the Conners Parent Rating Scale revealed a decrease on all subscales. Scores on the Conners Teacher Rating Scale were less conclusive. A follow-up revealed that most gains were maintained, but at a slightly lower level. (KW)